Monetary Policy Rate And Poverty Reduction In Nigeria: The Role Of Microfinance Banks - Tolulope-Femi Adesina; Damilola Ayomiposi Makinde; Alexander Ehimare Omankhanlen (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2025)
Poverty remains a major socio-economic challenge in Nigeria, despite the expansion of microfinance banking aimed at enhancing credit access for low-income groups. However, the effectiveness of microfinance banks (MFBs) in reducing poverty is increasingly shaped by macroeconomic conditions, particularly the Monetary Policy Rate (MPR), which sets benchmark interest rates across the financial system. High MPRs raise borrowing costs, making loans less affordable for the poor and small-scale entrepreneurs who depend on MFBs for credit. This study investigates the impact of changes in the MPR on poverty reduction in Nigeria, focusing on how monetary policy influences the lending capacity of microfinance institutions. The study is theoretically grounded primarily in the Keynesian Theory of Interest Rate and Investment and the Monetary Transmission Mechanism Theory, which explain how changes in interest rates influence investment and credit flows in the economy. The Credit Rationing Theory further informs understanding of how lending constraints affect credit availability for low-income borrowers. A quantitative approach is adopted, using quarterly time-series data from 2008 to 2023. The Johansen Cointegration Test and Vector Error Correction Model (VECM) are employed to examine both long-run and short-run relationships among key variables. Results show that a 1% increase in MPR leads to an estimated 0.48 percentage point rise in the national poverty rate. In contrast, increases in the loan-to-deposit ratio and capital adequacy ratio of MFBs are associated with reductions in poverty levels. The study concludes that monetary policy decisions significantly affect poverty outcomes through their influence on microfinance operations. It recommends that policymakers adopt inclusive monetary strategies that support affordable microcredit, while maintaining macroeconomic stability, to enhance financial inclusion and reduce poverty.